(3aGYdjI HQfGeL CfTWI afjI JTcjdjI dNaV MOI GdSdhc GdfeWi dOi YjfI ef GdCWaGd GdPGJhjjf (B/ s - (3UHQi YHOGdeMSf eMeO s; (3GMeO Gejf ehSi (B: s; (3NGdO YHOGdQGRb GdfLGQ (B: s; (3YRI YHOGdefYe QVhGf (B: s ((3GdbGgQI (B: s (3UHQi YHOGdeMSf eMeO (B: s, 2016)
(3gOa GdOQGSI JhXja GdCfTWI GdafjI GdJTcjdjI ai NaV MOI GdSdhc GdfeWi ddCWaGd GdPGJhjjf ef NdGd CfTWI GdHQfGeL(B. (3GLQGAGJ GdOQGSI Je GLQGA OQGSI Ydi YOO (B(10) (3CWaGd (B(5) (3PchQ h (B(5) (3EfGK ef GdCWaGd GdPGJhjjf JQGhMJ CYeGQge ef (B(5-7) (3SfhGJ hJe JWHjb(B: (3ebjGS Si Gjg(B.(3CQ(B.(3ES(B: (3h ebjGS GdSdhcjGJ GdfeWjI(B: (3h HQfGeL GdCfTWI GdafjI GdJTcjdjI(B. (3h Je JWHjbg Ydi YjfI GdHMK eJeKd ai YOO (B(48) (3LdSI HhGbY (B(12) (3CSHhY (B(4) (3LdSGJ CSHhYjI(B. (3fJGFL GdOQGSI(B: (3JhLO aQhb PGJ OdGdI EMUGFjI Hjf eJhSW QJH OQLGJ GdCWaGd GdPGJhjjf ai GdbjGSjf GdbHdi h GdHYOi dJWHjb HQfGeL GdCfTWI GdafjI GdJTcjdjI Ydi ebjGS GdSdhc GdfeWi ai ebjGS (B((3GdTOI(B) (3ai GJLGg GdJWHjb GdHYOi(B. (3JhLO aQhb PGJ OdGdI EMUGFjI Hjf eJhSW QJH OQLGJ GdCWaGd GdPGJhjjf ai GdbjGSjf GdbHdi h GdHYOi dJWHjb HQfGeL GdCfTWI GdafjI GdJTcjdjI Ydi ebjGS GdSdhc GdfeWi ai ebjGS (B((3GdJcQGQ(B) (3ai GJLGg GdJWHjb GdHYOi(B. (3dG JhLO aQhb PGJ OdGdI EMUGFjI Hjf eJhSW QJH OQLGJ GdCWaGd GdPGJhjjf GdPchQ h GdGfGK ai GdbjGS GdbHdi h GdHYOi dJWHjb HQfGeL GdCfTWI GdafjI GdJTcjdjI Ydi ebjGS GdSdhc GdfeWi ai ebjGS (B((3GdTOI h GdJcQGQ(B). (3dG JhLO aQhb PGJ OdGdI EMUGFjI Hjf eJhSW QJH OQLGJ GdCWaGd GdPGJhjjf ai GdbjGSjf GdHYOi h GdJJHYi dJWHjb HQfGeL GdCfTWI GdafjI GdJTcjdjI Ydi ebjGS GdSdhc GdfeWi ai ebjGS (B((3GdTOI(B). (3dG JhLO aQhb PGJ OdGdI EMUGFjI Hjf eJhSW QJH OQLGJ GdCWaGd GdPGJhjjf ai GdbjGSjf GdHYOi h GdJJHYi dJWHjb HQfGeL GdCfTWI GdafjI GdJTcjdjI Ydi ebjGS GdSdhc GdfeWi ai ebjGS GdJcQGQs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdJQHjI ddWahdI GdeHcQI (B- (3bSe GdYdhe GdfaSjIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdPGJhjIs; (3GdSdhc GdfeWis; (3CfTWI afjI JTcjdjIs